Proceedings of the 12th International Conference on Information Integration and Web-Based Applications &Amp; Services 2010
DOI: 10.1145/1967486.1967637
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge exploratory project for nanodevice design and manufacturing

Abstract: We are developing a framework for knowledge creation in nanodevice development, based on collaboration between nanodevice engineers and computer science researchers. Development of nanodevices requires a variety of knowledge; some of this knowledge is tacit, based on the user's experience. Therefore, it is difficult to become a good engineer in this development process. We propose the concept of "Evidence-based experiment planning" and develop a process for supporting experiment planning in nanodevice developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Previously, we have built an experimental record management system to analyze the results of experiments related to the development of nanocrystal devices [12]. Using pattern-mining techniques on this system, we found that different sets of parameters were used to form the same layer structure.…”
Section: Background and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have built an experimental record management system to analyze the results of experiments related to the development of nanocrystal devices [12]. Using pattern-mining techniques on this system, we found that different sets of parameters were used to form the same layer structure.…”
Section: Background and Motivationmentioning
confidence: 99%
“…However, the process of nanocrystal device development is not well systematized, requiring both engineering knowledge and craftsmanship [11]. We have been conducting a project called the "Knowledge Exploratory Project for diebt@kb.ist.hokudai.ac.jp Nanodevice Design and Manufacturing" to support the nanocrystal device development process [12]. This is a joint research project between the Research Center for Integrated Quantum Electronics (RCIQE) and the Division of Computer Science at Hokkaido University.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoinformatics is the science and practice of determining which information is relevant to the nanoscale science and engineering community, and then developing and implementing effective mechanisms for collecting, validating, storing, sharing, analyzing, modeling, and applying this information (De la Iglesia et al 2011). In order to support nanodevice development process, we have been working on a project that aims at analyzing the experiment results related to nanodevice development to provide insights for nanodevice novice researchers to help them planning their experiments more effectively (Yoshioka et al 2010). In this project, we have proposed a framework to annotate useful information from research papers related to nanodevice development (e.g., source material, evaluation parameter, and so on), and use them for analyzing experiment results (Dieb et al 2011).…”
Section: Introductionmentioning
confidence: 99%